Next-generation RNA vaccines - Blakney, Anna (Henry Stewart Talks, 2025)
State-of-the-field of RNA vaccines and therapies, Self-amplifying RNA (saRNA) 101, The differences between saRNA and mRNA, Novel saRNA vectors, Minimizing immunogenicity of lipid nanoparticles (LNPs)